ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN MEMBELI DI HERO PASAR SWALAYAN SURABAYA - Yazid Yud Padmono (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
This research is aimed at finding out factors that influence custemers buy in Hero Super Market. Some conclusion from the research result are: (1). Results of correlation matrix indicate relations among vatriables in the population.I can be seen from value of barlett’s test of spherity as many as 2298.599 and value of Kaiser-Mayer-Olhin o,601. It means analysis of significant factor to analyze the matrix correlation,because its value > 0,50. (2).Results of  factor analyses indicate cumulative petrcentage as much as 60.10 %, it shows that the research is able to explain factors that influence attitudes of consumers indeciding to  buy in Hero Super Market  Surabaya, while the remaining 39.90 % influenced by others factors. (3).Through rotation by way of using factor analysis from 26 variables summarized into 22 variables and classified into 9 component or core factor.